The Catalina Surveys Southern periodic variable star catalogue. Issue 3 (6th May 2017) - Drake, A. J.; Djorgovski, S. G.; Catelan, M.; Graham, M. J.; Mahabal, A. A.; Larson, S.; Christensen, E.; Torrealba, G.; Beshore, E.; McNaught, R. H.; Garradd, G.; Belokurov, V.; et al.
Abstract: Here, we present the results from our analysis of 6 yr of optical photometry taken by the Siding Spring Survey (SSS). This completes a search for periodic variable stars within the 30 000 deg 2 of the sky covered by the Catalina Surveys. The current analysis covers 81 million sources with declinations between −20° and −75° with median magnitudes in the range 11 < V < 19.5. We find approximately 34 000 new periodic variable stars in addition to the ∼9000 RR Lyrae that we previously discovered in SSS data. This brings the total number of periodic variables identified in Catalina data to ∼110 000. The new SSS periodic variable stars mainly consist of eclipsing binaries, RR Lyrae, LPVs, RS CVn stars, δ Scutis, and Anomalous Cepheids. By cross-matching these variable stars with those from prior surveys, we find that ∼90 per cent of the sources are new discoveries and recover ∼95 per cent of the known periodic variables in the survey region. For the known sources, we find excellent agreement between our catalogue and prior values of luminosity, period, and amplitude. However, we find many variable stars that had previously been misclassified. Examining the distribution of RR Lyrae, we find a population associated with the Large Magellanic Cloud (LMC) that extends more than 20° from its centre confirming recent evidence for the existence of a very extended stellar halo in the LMC. By combining SSS photometry with Dark Energy Survey data, we identify additional LMC halo RR Lyrae, thus confirming the significance of the population.